Principios básicos de los acuerdos de compensación de los servicios ecosistémicos de las microcuencas Rumiyacu, Mishquiyacu y Almendra - Vilca Lucana, Rita (2011)
In Moyobamba city, the water supply in quantity and quality necessary for the human· consumption, as well as for the agricultura! and industrial use there is turning into a problem increasingly serious, caused principally for the forest loss, into the areas of conservation, which reduces the available quantity of water in epoch of low water and in consequence affects his quality. Natural ecosystems generate multiple benefits, including the provision of water, soil conservation, the beauty of the landscape as a space for recreation, habitat for flora and fauna, as well as the purification of the air and the carbon fixation. Faced with this problem is implementing a mechanism of "Compensation for Ecosystem Services" (CES), which is a mechanism to finance the conservation of biological diversity and ensure the supply of ecosystem services; the conservation area of the microwatersheds Rumiyacu, Mishquiyacu and Alllmedra, as these are of vital importance for the supply of potable water to the Moyobamba city. This mechanism works for the conservation and reforestation of forest, conservation area mainly from the headwaters ofthe ravines. The CES seeks to establish commitments among rural families settled in the upper parts of the watershed and the plaintiffs in the water in the low parts. These commitments include the bidders will have multiple benefits, as well as, technical advice in their crops, forestry management, tree nurseries, compost, organic fertilizers deployment of improved stoves, beekeeping, latrines, etc. With the purpose and principal aim to realize a sustainable managing of the ecosystems that shape the area.